Detection of Social Proximity and Sanctions on PBB Tax Compliance: Quasi-Experiment in Pangkalpinang City - Wardhani, Rulyanti Susi; Nugroho, Sigit; Rudianto, Nur Ahmad Ricky (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
Tax compliance studies often focus on legal sanctions, while social factors receive relatively less attention. This study aims to examine the effects of social proximity and sanctions on taxpayer compliance concerning the Rural and Urban Land and Building Tax (PBB-P2) in Pangkalpinang City. Sixty-five taxpayers participated in a quasi-experimental pretest–posttest intervention that included neighborhood discussions led by community leaders and reminders of social and administrative sanctions. Compliance rose after the intervention, as indicated by Spearman's correlation and the Wilcoxon test. The findings indicate that social proximity and perceived sanctions are positively associated with taxpayer compliance, and that community expectations and social norms function as informal social control that complements formal sanctions. These findings imply that integrating community-based and educational approaches with sanction enforcement can enhance local tax compliance, particularly in tightly knit cities like Pangkalpinang.